Genetic Framework of Cyclin-Dependent Kinase Function in Arabidopsis - Nowack, Moritz K.; Harashima, Hirofumi; Dissmeyer, Nico; Zhao, Xin'Ai; Bouyer, Daniel; Weimer, Annika K.; De Winter, Freya; Yang, Fang; Schnittger, Arp (Developmental cell, 2012)
Cyclin-dependent kinases (CDKs) are at the heart of eukaryotic cell-cycle control. The yeast Cdc2/CDC28 PSTAIRE kinase and its orthologs such as the mammalian Cdk1 have been found to be indispensable for cell-cycle progression in all eukaryotes investigated so far. CDKA;1 is the only PSTAIRE kinase in the flowering plant Arabidopsis and can rescue Cdc2/CDC28 mutants. Here, we show that cdka;1 null mutants are viable but display specific cell-cycle and developmental defects, e.g., in S phase entry and stem cell maintenance. We unravel that the crucial function of CDKA;1 is the control of the plant Retinoblastoma homolog RBR1 and that codepletion of RBR1 and CDKA;1 rescued most defects of cdka;1 mutants. Our work further revealed a basic cell-cycle control system relying on two plant-specific B1-type CDKs, and the triple cdk mutants displayed an early germline arrest. Taken together, our data indicate divergent functional differentiation of Cdc2-type kinases during eukaryote evolution. [Display omitted] ► Mutants for CDKA;1, the only PSTAIRE CDK in Arabidopsis, are viable ► cdka;1 mutants show specific cell-cycle and cell-differentiation defects ► The key substrate of CDKA;1 function is the Rb homolog RBR1 ► PSTAIRE and plant-specific CDKs have overlapping functions in both G1/S and G2/M Nowack et al. find that mutants in CDKA;1, the only canonical PSTAIRE cyclin-dependent kinase (CDK) in Arabidopsis, are viable. CDKA;1's primary role during S phase entry is to regulate RBR1, an Rb homolog; however, plant-specific B1-type CDKs and CDKA;1 are partially redundant, sharing multiple roles throughout the cell cycle.